PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN MAS KOKI (Carassius auratus) PADA SUMBER MATA AIR BERBEDA DI RUANG SEMI OUTDOOR - Arfan Afandi; Wardha Jalil (Jurnal Akuakultur Rawa Indonesia, 2023)
The purpose of this study was to determine the growth and survival rates of goldfish (Carassius auratus) with different sources in semi outdoor space. The design used in this study was a completely randomized design (CRD) consisting of 3 (three) treatments namely Treatment A (Kali Bungi Spring), Treatment B (La Sura Spring), and Treatment C (Uwe Balanga Spring). Each treatment was repeated three times so that there were 9 units. Each treatment consisted of 5 goldfish. The parameters observed were absolute weight gain, specific growth rate, survival rate, feed conversion ratio, and water quality measurements. Based on the results of the research and discussion above, it can be concluded that rearing goldfish (Carassius auratus) in semi-open spaces has a significant effect on absolute growth, but has no significant effect on specific growth rate and feed conversion and survival. Water quality parameters in three springs are still in the proper category to support the cultivation of goldfish (Carrasius auratus).Keywords : Growth, survival rate, Springs, Goldfish Chef.